Study on the impact of industrial and commercial capital going to the countryside on non-grain production of cultivated land—based on the provincial panel data of China from 2013 to 2022 - Yang, Hongli; Wang, Fengjuan (Frontiers in Sustainable Food Systems, 2025)
Industrial and commercial capital going to the countryside can effectively alleviate the shortage of funds for agricultural and rural development, which is the key to promote the modernization of agriculture and rural areas. In order to explore the influence of industrial and commercial capital going to the countryside on the non-grain production of cultivated land, based on the panel data of 30 provinces (except Tibet) in China from 2013 to 2022, this paper systematically uses the two-way fixed effect model, the intermediary effect model and the threshold effect model to test the effect, mechanism and threshold effect of industrial and commercial capital going to the countryside on the non-grain production of cultivated land. The results show that: (1) Industrial and commercial capital going to the countryside can effectively restrain the non-grain production of cultivated land. (2) Industrial and commercial capital going to the countryside can restrain non-grain production of cultivated land by accelerating land circulation and improving the level of scientific and technological development. (3) There is a single threshold effect on the inhibition of industrial and commercial capital going to the countryside. When the level of industrial and commercial capital going to the countryside is higher than the threshold value (29.124), the inhibition on non-grain production of cultivated land is weakened. (4) The inhibitory effect of industrial and commercial capital going to the countryside is heterogeneous, which has a greater inhibitory effect on the non-grain production of cultivated land in central China, major grain producing areas, northern region and areas with low marketization. This study enriches the research on the influence of industrial and commercial capital going to the countryside on the production and use of cultivated land, and provides theoretical reference for guiding industrial and commercial capital to invest in agriculture and promoting the sustainable development of agriculture.